Effect of La-concentration (x) on some physical properties of LaxSm1-xS (x = 0, 0.1, 0.25 and 0.35) alloys - Benmakhlouf , Abdelfateh; Mezouar , Rabie; Daoud, Salah (International Journal of Scientific World, 2024)
In the present work, we studied the effect of the incorporation of Lanthanum (La) atoms into Samarium monosulfide (SmS) small gap mag-netic semiconductor birary compound. So some physical properties of pure (SmS) and La-doped SmS compound LaxSm1-xS (x = 0.1, 0.25 and 0.35) ternary alloys) were obtained. We found that the longitudinal wave velocity of LaxSm1-xS ternary alloys decreases monotonically and non-linearly with increasing La-concentration (x) from 0 to 35%, while the transverse and average elastic wave velocities, Debye tem-perature and Vickers Hardness for LaxSm1-xS (x = 0, 0.1, 0.25 and 0.35) ternary alloys change non-monotonically and varied non-linearly with increasing La-concentration (x). For LaxSm1-xS (x = 0.1, 0.25 and 0.35) ternary alloys, the lattice parameters and the elastic constants used here are taken from the work of Schärer and Wachter (Solid State Communications, Vol. 96, No. 7, (1995), pp. 497–501), while for SmS divalent chalcogenide birary compound, the elastic constants used here are taken from the book edited by Sirdeshmukh et al. (D. B. Sirdeshmukh, L. Sirdeshmukh, K. G. Subhadra, Micro-and macro-properties of solids, Springer-Verlag Berlin Heidelberg, 2006, page 269). The Debye temperature was calculated using two different approches (Debye’s approch and Blackman’s approch) To the best of author knowledge, there is no any data in the literature on the Debye temperature and the minimum thermal conductivity for LaxSm1-xS (x = 0.1, 0.25 and 0.35) ternary alloys to make comparaison.